Catalytic hydrodeoxygenation of 2-methoxy phenol and dibenzofuran over Pt/mesoporous zeolites. (1st March 2015) - Lee, Hyung Won; Jun, Bo Ram; Kim, Hannah; Kim, Do Heui; Jeon, Jong-Ki; Park, Sung Hoon; Ko, Chang Hyun; Kim, Tae-Wan; Park, Young-Kwon
Abstract: The hydrodeoxygenation of 2-methoxy phenol and dibenzofuran, which are representative model compounds of bio-oil, was performed using two different Pt/mesoporous zeolite catalysts, Pt/mesoporous Y and Pt/mesoporous MFI. The reforming of 2-methoxy phenol and dibenzofuran via catalytic hydrodeoxygenation was investigated using a batch reactor at 40 bar and 250 °C. The characteristics of the catalysts were analyzed by N2 adsorption-desorption, X-ray diffraction, and NH3 temperature programmed desorption. Pt/mesoporous zeolite catalysts containing both strong acid sites and mesopores showed the higher conversion of 2-methoxy phenol than Pt/SiO2 and Pt/Si-MCM-48 with no acid sites, Pt/γ-Al2 O3, and a mixture of mesoporous Y and Pt/SiO2, indicating the importance of both Pt and strong acid sites for high catalytic activity. Among the two Pt/mesoporous zeolite catalysts tested, the conversion of 2-methoxy phenol to cyclohexane over Pt/mesoporous Y was much higher than that over the Pt/mesoporous MFI. This was attributed to the better textural properties, such as surface area, pore volume and micropore size, compared to those of Pt/mesoporous MFI. The catalytic conversions of dibenzofuran obtained using two Pt/mesoporous zeolite catalysts were similar and the main products were 1, 1′-bicyclohexyl, cyclopentylmethyl-cyclohexane and cyclohexane. In addition, the reaction mechanisms of 2-methoxy phenol and dibenzofuran over Pt/mesoporous zeolite were suggested. Highlights: HDO of 2-methoxy phenol and dibenzofuran was performed over Pt/mesoporous zeolites. Pt/mesoporous zeolites have mesopores and strong acid sites. Main product of HDO of 2-methoxy phenol was cyclohexane. Main products of HDO of dibenzofuran were bicyclohexyl (BCH), i -BCH, and cyclohexane.